Tim-3 Relieves Experimental Autoimmune Encephalomyelitis by Suppressing MHC-II - Tang, Lili; Li, Ge; Zheng, Yang; Hou, Chunmei; Gao, Yang; Hao, Ying; Gao, Zhenfang; Mo, Rongliang; Li, Yuxiang; Shen, Beifen; Wang, Renxi; Wang, Zhiding; et al. (Frontiers in Immunology, 2022)
Tim-3, an immune checkpoint inhibitor, is widely expressed on the immune cells and contributes to immune tolerance. However, the mechanisms by which Tim-3 induces immune tolerance remain to be determined. Major histocompatibility complex II (MHC-II) plays a key role in antigen presentation and CD4+T cell activation. Disregulated expressions of Tim-3 and MHC-II have been found to be associated with the pathogeneisis of many autoimmune diseases including multiple sclerosis. Here we demonstrated that, by suppressing MHC-II expression in macrophages via the STAT1/CIITA pathway, Tim-3 inhibits MHC-II mediated autoantigen presentation and CD4+T cell activation. As a result, overexpression or blockade of Tim-3 signaling in mice with experimental autoimmune encephalomyelitis (EAE) inhibited or increased MHC-II expression respectively and finally altered clinical outcomes. We thus identified a new mechaniams by which Tim-3 induces immune tolerance in vivo and regulating the Tim-3-MHC-II signaling pathway is expected to provide a new solution for multiple sclerosis treatment.